The Internment and Repatriation of the Japanese-French Nationals Resident in New Caledonia, 1941–1946 - Rowena Ward (PORTAL: Journal of Multidisciplinary International Studies, 2017)
The pre-1941 Japanese population of New Caledonia was decimated by the French administration’s decision to transfer most of the Japanese residents to Australia for internment at the outbreak of the Asia-Pacific theatre of the Second World War. Among the men transferred to Australia were ten men who had been formerly French nationals but had lost their French nationality by decree. The French Administration’s ability to denationalise and intern and then subsequently repatriate the former-Japanese French-nationals was possible due to changes to the French nationality laws and regulations introduced by the Vichy regime. This paper considers the case of the Japanese who had taken French nationality and were denationalised in the context of the changes to the French nationality laws that, in turn, negatively affected the post-1945 sustainability of the Japanese community in New Caledonia.